The Implementation of the Main Duties and Functions of the School Principal for the Computer-Based National Assessment - Riawan, I Nyoman; Darmada, I Made; Chandrawati, Titi (Edukasi, 2023)
A principal is a teacher who is given the additional duty of being the highest leader in an educational institution and has to be responsible for everything related to the smooth running of the school for the realization of the school's goals. Furthermore, the main duties and functions of the principal are the primary obligations of a person who serves as a school principal to achieve national education goals, especially the ANBK [Computer-Based National Assessment] implementation at the elementary school level. This research aimed to analyze and describe the implementation of the main duties and functions of the school principal in the 2021 ANBK in Gugus V SD Kediri District, Tabanan Regency. This research used a qualitative method. In collecting data, the researcher used observation, interviews, and documents. The research results showed the main duties and functions of the school principal for the ANBK are managerial, entrepreneurial, and supervisory.